2014
DOI: 10.1097/mca.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate recovery after exercise and its relation with neutrophil-to-lymphocyte ratio in patients with cardiac syndrome X

Abstract: CSX patients have higher NLR and PLR and slower HRR and lower DTS, similar to CAD patients, suggesting that CSX patients may be at a higher risk for developing cardiovascular events in the future. NLR may predict autonomic imbalance assessed by HRR in CSX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…In contrast, patients with stable CAD had a lower mean NLR of 2.8 [8] compared with patients with STEMI. Patients with cardiac syndrome X had a mean NLR of 3.1 [20]. In a general population, the mean NLR was 2.2 [15].…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, patients with stable CAD had a lower mean NLR of 2.8 [8] compared with patients with STEMI. Patients with cardiac syndrome X had a mean NLR of 3.1 [20]. In a general population, the mean NLR was 2.2 [15].…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that ratios of neutrophil and platelet counts to lymphocyte count (neutrophil-to-lymphocyte ratio, NLR and platelet-to-lymphocyte ratio, PLR) were potential inflammatory markers that are closely related to the prognosis of chronic inflammatory and cardiovascular diseases (4)(5)(6)(7)(8)(9)(10)(11)(12). In addition, NLR and PLR parameters were associated with C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) values that play an important role in the pathogenesis of HF (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of evidence in recent years has demonstrated that cardiac autonomic nervous activity, as evaluated by heart rate variability (HRV) and HRR, is associated with inflammatory markers [ 25 , 26 ]. More recently, we have shown that impaired cardiac autonomic function, as evidenced by a slower HRR, is closely related to inflammatory markers such as hsCRP in both CAD and cardiac syndrome X [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…HRR was described as the change in heart rate from peak exercise to 1 min after exercise. HRR of 12 beats/min or less was defined as abnormal [ 9 - 11 ]. In addition, the Duke treadmill score (DTS) was calculated for each participant according to the following formula: DTS = (exercise duration in minutes) - (5 × ST deviation in millimeters) - (4 × treadmill angina index).…”
Section: Methodsmentioning
confidence: 99%